State aid modernization and its implications for the assessment of large investment projects: The relevance of market screens in the regional aid guidelines - Hans W. Friederiszick; Nicola Tosini (European School of Management and Technology (ESMT), 2012)
The Regional Aid Guidelines foresee specific screens for an in-depth assessment of Large Investment Projects (LIPs): an in-depth assessment is initiated if the market share of the aid beneficiary is above 25% or the investment results in a capacity expansion above 5% in a declining market. It is currently being discussed within the broader State Aid Modernization package and also due to a recent court ruling on the case Propapier whether these market screens should stay as they are. Based on a dataset of all LIP cases notified under the 2006 Regional Aid Guidelines, we evaluate those market screens and find that the screens do have power to identify problematic cases cases with a below average expected aid effectiveness and aid measures targeting specific industries. We also find, however, that the market screens are affected by a severe implementation problem and, hence, do not help to shorten phase I investigations. From a conceptual perspective, they are also not capable of identifying some of the potentially most problematic regional State aid cases. Policy options are discussed.
urn:nbn:de:101:1-201303269153
Keywords: H81; L4; O25; R58; 650; competition policy; regional state aid; subsidies; anti-competitive effects